From Anthropocentrism to Ecocentrism: Integrating the Rights of Nature into Sri Lanka’s Legal Framework to Address Industrial Water Pollution - A Comparative Analysis of Ecuador, New Zealand, And India - Jayawardana, Y.P.N.; Peiris, K.P.S.G. (Faculty of Arts, University of Jaffna & Surana and Surana International Attorneys, 2026)
The swift industrial development in Sri Lanka, amidst such rapid industrialisation, has produced a long-lasting economic growth along with severe environmental degradation, the most apparent of these being industrial water pollution. The discharge of effluents from textile, rubber processing and tanneries to rivers and water resources has led to ecological degradation, depletion of biodiversity and increased health hazards for water-based communities. Despite the existence of statutory instruments such as the National Environmental Act, this article asserts that Sri Lanka’s environmental management regime continues to be based on anthropocentrism by treating nature as a resource under the control of human beings for their own purpose rather than valuing it in its own right and deserving of independent legal recognition and protection. This anthropocentric, curative approach has been structurally unable to prevent environmental damage or to secure ecosystemic restoration. Building upon ecocentric legal theory, this article develops the Rights of Nature as a reframing of environmental law regulation. The Rights of Nature approach breaks down the property paradigm of nature and acknowledges that ecosystems are rights-bearing entities with the right to exist, flourish, regenerate, and be restored. Operations which provide legal personality to natural entities reframe environmental harm as a transgression of ecological rights, instead of just an infringement on human interests and consequently enhance the enforceability and access to justice. Methodologically, the article engages in doctrinal and comparative legal analysis, focusing on Sri Lanka’s legislative regime, juridical responses and key industrial water pollution incidents such as the Rathupaswala drinking water crisis, Kelani River diesel spill and Chunnakam groundwater contamination. These accounts of domestic failings are then measured against international examples of Rights of Nature, specifically Ecuador’s constitutional recognition of the rights of nature, New Zealand’s legal personhood model to the Whanganui River, and India’s judicial recognition of the legal personhood of the Ganga and Yamuna rivers The article maintains that embedding Rights of Nature within Sri Lanka’s legal system through constitutional interpretation, statutory reform and judicial creativity provides a principled ecocentric solution to industrial water pollution. It argues that harmonizing human and ecological rights is particularly important for forging environmental justice, sustainable development, and lasting water security in Sri Lanka.
Keywords: Rights of nature; Industrial water pollution; Anthropocentrism; Legal personhood; Environmental justice